Reservoir modelling to assess the releases and energy generation for a projected scenario of Tarbela reservoir in Pakistan - Saqib Ehsan; Muhammad Usman; Muhammad Ahmed Munir; Abdullah Akram; Muhammad Taqi (Penerbit Universiti Kebangsaan Malaysia, 2024)
Reservoirs are normally formed by the construction of dams across rivers, but off-channel reservoirs may be provided by diversion structures and canals or pipelines that convey water from a river to natural or artificial depressions. The behaviour of the flow due to construction of dam leads to change in a fluvial process leads to deposition of sedimentation in reservoir. In this research, reservoir modelling has been carried out by using HEC-ResSim for Tarbela reservoir in Pakistan. In Pakistan, the Tarbela Reservoir is the largest reservoir on Indus River and it is the backbone of Pakistan’s agriculture sector and economy. The model was calibrated for year 2014 and validated for year 2020 in terms of outflow and power generation. The results show close comparison between simulated and observed outflow and power values for different scenarios. On the basis of 30-year histogram cycle, the future prediction of releases/outflows, power/energy generation in year 2035 has also been made. After 2035, Tarbela reservoir is expected to become the run-off the river type project due to decrease in the gross storage capacity. As per simulated results of the projected scenario (2035), the releases/outflows from reservoir and energy generation will increase in summer season by 7% and 36% respectively and decrease in winter season by 50% and 37% respectively. Further, the reduction in gross storage capacity due to sedimentation would result in the reduction of annual energy generation by 6.5% in year 2035.